Anionic and Cationic Dyes Removal from Aqueous Solutions by Adsorption onto Synthetic Mg/Al Hydrotalcite-Like Compound - Eddy Heraldy; Sri Juari Santosa; Triyono Triyono; Karna Wijaya (Universitas Gadjah Mada, 2015)
The current investigation reports an effective adsorption of both anionic species and cationic dyes on Mg/Al hydrotalcite-like compounds (Mg/Al HTlc) synthetic from brine water, as novel, inexpensive available alternative to the commercial hydrotalcite. The feasibility of the Mg/Al HTlc, for the adsorptive removal of both anionic (Eosin Yellow-EY and Methyl Orange-MO) and cationic (Methylene blue-MB) dyes from aqueous solution was evaluated in a batch process. Dyes adsorption process was thoroughly studied from both kinetic and equilibrium points of view for all adsorbents. The adsorption kinetics was tested for the pseudo-first order and pseudo-second order kinetic models at different experimental conditions. The dyes adsorption follows the pseudo-second order kinetics model, with correlation coefficients close to unity when experimental data were fitted in the model. The experimental isotherm data were analyzed using Langmuir and Freundlich isotherms. The results from Langmuir isotherm indicated that the capacity of Mg/Al HTlc for the adsorption of anionic dyes was higher than that for cationic dyes.